PHOTOVOLTAIC AND WIND TURBINE: A COMPARISON AS BUILDING INTEGRATED RENEWABLE ENERGY IN INDONESIA - Susan, Susan; Wardhani, Dyah Kusuma (Humaniora, 2020)
The research tried to comprehensively review the systems related to Building Integrated Photovoltaic (BIPV) and Building Integrated Wind Turbine (BIWT). The review aimed to observe the advantages and disadvantages of the application. Designers could use that comparison for consideration of choosing the most suitable Building Integrated Renewable Energy (BIRE) concept for projects. The research presented a literature review of BIRE systems, particularly on BIPV and BIWT systems. The critical analysis focused on some parameters related to their main energy source, type, influencing factor, efficiency, and boundary. The observation about BIPV would be divided into subgroups according to photovoltaic (PV) materials, modules, efficiency, performance?s boundaries, and the general rule of thumb of its installation. The research finds that the BIPV application has advantages in terms of the building?s application scale. It can be applied from small-scale to large-scale. Furthermore, the BIPV application does not need extra space and could directly replace the conventional building envelope materials. The issues of non-uniformity and heat transfer in BIPV can be solved by installing PV in folding-concept and placed an air gap with fins inside. On the other hand, BIWT also has an abundant energy source, but the application limits to windy areas (rural areas or urban areas in high elevation). Aside from those limitations, the BIWT application also has issues of structure, noise, and aesthetical value.